Randomized controlled trial of multidisciplinary rehabilitation therapy using mobile applications in cases of ankle fractures - Petya Kasnakova; Anna Mihaylova; Boris Djurdjev; Biyanka Tornyova (PAGEPress Publications, 2022)
A multidisciplinary approach to rehabilitation in patients with ankle fractures is needed to return to their daily activities. Mobile health applications can improve or optimize the rehabilitation process. The purpose of this study is to monitor the efficiency of a modified and validated rehabilitation scheme for the functional rehabilitation of the lower limbs. The subjects of the study are patients in the post-immobilization and post-operative period. The algorithm of procedures administered to the patients were performed by physiotherapists and monitored via mobile apps. The results show a reduction of the swelling and the pain, overcoming the muscular imbalance, enhanced stabilization, correct way of walking, and an improved quality of life of the patients with ankle fractures. Despite a certain trend towards residual deficit, the implementation of kinesitherapeutic means creates the necessary background on the basis of which specialized methods can be applied - joint-mobilizing techniques and passive stretching, for the purpose of the full recovery of the functions of the lower extremity. The application of mobile apps optimizes the recovery process and increases access to rehabilitation.